Предмет: Математика,
автор: МаШуТКа2003
(4 2/11- 1 6/11) + 7 4/11-(9/11+ 3 7/11) помогите срочно
Ответы
Автор ответа:
0
(4 2/11- 1 6/11) + 7 4/11-(9/11+ 3 7/11) =
1) 4 2/11- 1 6/11 = 2 7/11
2) 9/11+ 3 7/11 = 3 16/11
3) 2 7/11+ 7 4/11 = 9 11/11 = 10
4) 10 - 3 16/11 = 5 6/11
То есть (4 2/11- 1 6/11) + 7 4/11-(9/11+ 3 7/11) = 5 6 /11
1) 4 2/11- 1 6/11 = 2 7/11
2) 9/11+ 3 7/11 = 3 16/11
3) 2 7/11+ 7 4/11 = 9 11/11 = 10
4) 10 - 3 16/11 = 5 6/11
То есть (4 2/11- 1 6/11) + 7 4/11-(9/11+ 3 7/11) = 5 6 /11
Автор ответа:
0
спасибо большое))
Похожие вопросы
Предмет: Биология,
автор: kapkanchick
Предмет: История,
автор: kozyrewadarjamax
Предмет: Литература,
автор: Abbbyou
Предмет: Алгебра,
автор: inkognito1t
Предмет: Алгебра,
автор: polina090997